Drillhole Detonation Method to evaluate in situ stresses in Marañón of Poderosa mining company - Berrocal Mallqui, Miguel Angel (2023)
To construct any underground excavation, it is required to know the magnitude and influence of in situ stresses in the excavation; there are methods to evaluate the stresses, such as Lithostatic loading, Overcoring, Hydraulic fracturing; each with its advantages and limitations. The present Drillhole Detonation Method has the purpose of evaluating the in situ stresses with: easy application, low cost, and its results are provided on site. The Drillhole Detonation Method; interprets the radial fractures produced around the detonated drillholes; crediting: stress ellipse, direction of the major stress σ1, calculation of the value of parameter k, and the estimation of the Correction Factor (CF) value. The formulation is adapted from the Lithostatic load method to evaluate the stresses σh and σv. The Drillhole Detonation Method was applied in Marañón of Poderosa mining company, evaluating and randomly selecting 9 stations, and at a global level it was calculated: direction of the major stress 75°, coefficient k = 0.79, major stress σ1 = 25.19 MPa, and minor stress σ3 = 15.44 MPa.